The Contribution of Mobile Game Addiction To Student Academic Procrastination - Muhammad Alfi Syahrin; Zadrian Ardi (Jurnal Aplikasi IPTEK Indonesia, 2020)
Procrastination is a tendency to delay the completing of a task or job. Meanwhile, academic procrastination is the behavior of procrastinating on the completion academic task. There are several characteristics of academic procrastination, one of which is doing other activities that are considered more fun, one of which is playing mobile games that can be accessed through gadgets owned by individuals. This study aims to describe mobile games addiction, academic procrastination, and examine the contribution of mobile games addiction to student’s academic procrastination. This research is a descriptive correlational study with quantitative research methods. This research sample using purposive sampling technique by taking a sample of students of MAN 1 Padang City who tended to experience addiction to mobile games with a percentage ?50%. The number of samples is this study were 101 students. Data analysis in this study used descriptive analysis with percentages and simple linear reggresion analysis. The results showed that in general the level of student mobile game addiction was in the medium category, in general the level of student academic procrastination was in the medium category, and there was a significant contribution of mobile game addiction to student academic procrastination.